Illuminated Manuscript 626 C from the Treasury of Split Cathedral – Riddles and Suppositions - Jozić, Branko (Poznańskie Studia Slawistyczne, 2018)
The collections in Croatian churches and monasteries keep treasure of outstanding cultural and historical value, which is still waiting to be studied, properly evaluated and published. Among just such precious items is a composite, acephalic and lacunose manuscript codex from the turn of the 12th and 13th centuries, which is kept in the treasury of Split Cathedral (626 C). Although it is handsome, rich in various data and very interesting, in the last hundred or so years since it was rediscovered, it has not attracted any great attention from the cultural or the scholarly public. Here is set out a codicological description listing all the anomalies and damages, established the contents and authorship of the texts; at the end some assumptions and arguments backing them up will be put forward as well as some indications of its subsequent fortune.